2014 IEEE Energy Conversion Congress and Exposition (ECCE) 2014
DOI: 10.1109/ecce.2014.6953631
|View full text |Cite
|
Sign up to set email alerts
|

Methods for reducing leakage electric field of a wireless power transfer system for electric vehicles

Abstract: A wireless power transfer system for electric vehicles has to deal with the issue of high leakage levels of electric field. In this paper, we propose two methods for reducing the leakage electric field. First is the use of ferrite to reduce the emitted leakage electric field to the environment. Second is the changing of the pulse width of the inverter to reduce the harmonics of leakage electric field. We present the experimental results of the reduction effects of leakage electric field. We also compared the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Therefore, several reduction methods were presented, such as using ferrite materials [14], metallic materials (aluminum) [178,179], and metamaterials (MM) [180][181][182][183]. Changing the pulse width of the inverter to decrease the harmonics of the leakage electric field was presented [184]. In [185], the authors presented three active methods that include the independent self-EMF cancelation (ISEC), the 3-dB dominant EMF cancel method (3DEC), and the linkage-free EMF cancel method (LFEC).…”
Section: Emf and Emi Mitigation Methodsmentioning
confidence: 99%
“…Therefore, several reduction methods were presented, such as using ferrite materials [14], metallic materials (aluminum) [178,179], and metamaterials (MM) [180][181][182][183]. Changing the pulse width of the inverter to decrease the harmonics of the leakage electric field was presented [184]. In [185], the authors presented three active methods that include the independent self-EMF cancelation (ISEC), the 3-dB dominant EMF cancel method (3DEC), and the linkage-free EMF cancel method (LFEC).…”
Section: Emf and Emi Mitigation Methodsmentioning
confidence: 99%
“…At the same frequency, the authors of Laakso et al (2014) investigated 7-kW WPT adopting a computational modelling to the electromagnetic field to humans. Jo et al (2014) have been shown a variation of the pulse width to reduce harmonics and leakage. Furthermore, Choi et al (2014b) presented three methods such as independent self-cancellation, the 3-dB dominant cancel method and the linkage free cancel method.…”
Section: Safetymentioning
confidence: 99%
“…There was a concern that using the filter would lead to a systemwide decline in efficiency, but the filter served to reduce the harmonic component of the input power supply. As a result, power transfer using the fundamental wave was possible and the leakage electromagnetic field of harmonics could be reduced [20]. As significant levels of power transfer are anticipated in dynamic power transfer, it is critical that the leakage electromagnetic field be reduced.…”
Section: Input Impedancementioning
confidence: 99%